2021
DOI: 10.4068/cmj.2021.57.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effect of Exercise Training with Whole Body Electric Muscle Stimulation Suit on Strength and Balance in Young Women: A Randomized Controlled Trial

Abstract: Many studies about Electrical muscle stimulation (EMS) have been performed to determine the effectiveness of EMS. However, most studies enrolled only elderly patients. Moreover, only a few studies have verified the effect of a whole body (WB)-EMS suit on young healthy women. Thus, the main purpose of this study was to verify the physiological effects of exercise training with a WB-EMS suit in young women. During the study periods, 24 young women were randomly assigned into two groups: 1) the WB-EMS training gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Mainly on body fat reduction, there are studies reporting significant differences for the WB-EMS group [16,52,56] and others in which its effects were not significant. [42,62] This heterogeneity, to a large extent, can be explained by 4 main factors: application of different types of intensity (from low to high intensity); different training volumes (from 20 to 90 minutes per week, from 6 weeks to 12 months of intervention); little or no control over participants' caloric intake in most studies; and different population types (WB-EMS, trained participants, healthy, obese, cancer patients, and others).…”
Section: Discussionmentioning
confidence: 99%
“…Mainly on body fat reduction, there are studies reporting significant differences for the WB-EMS group [16,52,56] and others in which its effects were not significant. [42,62] This heterogeneity, to a large extent, can be explained by 4 main factors: application of different types of intensity (from low to high intensity); different training volumes (from 20 to 90 minutes per week, from 6 weeks to 12 months of intervention); little or no control over participants' caloric intake in most studies; and different population types (WB-EMS, trained participants, healthy, obese, cancer patients, and others).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of perceived exertion is commonly used to control the intensity during the WB-EMS training [ 7 , 16 , 18 , 20 , 37 ]. We reported similar RPE data in the three experimental trials, slightly increasing along the sets in the bench press and the squat exercise, although with no significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the CK levels were under the damage threshold of 5000 U/L [ 19 ]. Other authors found significant differences in the isokinetic muscle function and balance functions in WB-EMS training [ 20 ], but there is still controversy about whether WB-EMS is a hazard and should not be used as a training modality.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the current is, in most cases, controlled by the Borg subjective perception scale (RPE) [ 18 , 28 , 29 ]. Recently, some authors have used the maximum stimulus tolerance to define the intensity of the current [ 30 , 31 ]. The total time of sessions is up to 20 min in the most relevant studies.…”
Section: Introductionmentioning
confidence: 99%